Representasi Ajaran Islam dalam Lagu Satu Karya Dewa 19 - Fadhel Muhammad (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2025)
This study examines the representation of Islamic teachings in the song Satu by Dewa 19 as a form of cultural da’wah through popular music. The research problem focuses on how Islamic values such as ukhuwah (brotherhood), tawhid (oneness of God), and tasamuh (tolerance) are reflected in the lyrics of a popular song that is not explicitly categorized as religious music. This topic is significant because it demonstrates that religious messages can appear in the sphere of popular culture and serve as an effective medium to strengthen unity within a multicultural society. The research employs a qualitative method with a content analysis approach, analyzing the song lyrics and relating them to Islamic sources such as the Qur’an, hadith, and classical Islamic literature. The findings reveal that the song Satu represents Islamic teachings on preserving brotherhood, reinforcing tawhid as the foundation of life, and promoting tasamuh to respect diversity. Furthermore, the song is highly relevant to contemporary society, particularly in pluralistic Indonesia, as it reinforces national and humanitarian values. This study concludes that popular music can serve as an alternative and effective medium of da’wah while enriching Islamic studies within the context of modern art and culture.